Acceptability of telephone support as perceived by patients with cancer: A systematic review. (30th January 2017) - Liptrott, S.; Bee, P.; Lovell, K.
Abstract : Telephone‐based interventions can increase accessibility to healthcare and are increasingly used as a convenient method of providing support. We conducted a systematic review of published literature reporting adult patients' perceptions of the acceptability of, and satisfaction with, telephone‐based interventions during or post‐treatment for cancer. Systematic searches identified 4, 855 articles. Forty‐eight articles describing 50 studies were included in the review. Three intervention categories were identified post hoc: (1) telephone follow‐up in lieu of routine hospital follow‐up, (2) telephone interventions for treatment side‐effect monitoring and toxicity management supplementary to usual care, and (3) supplementary psycho‐educational telephone interventions. Across studies, some consistent findings emerged. Positive perceptions emphasised the convenience of telephone interventions and increased accessibility to care. Conflicting perceptions of the quality of the support received, the impact of telecare on the patient–healthcare professional relationship and the need for such interventions emerged. In conclusion, the evidence base relating to patients' perceptions of telephone‐based interventions is increasing. Interpretation of findings is currently limited by methodological limitations in the primary research. The instruments chosen to assess patient satisfaction quantitatively do not always reflect the patient‐centred priorities that emerge from qualitative data. Subsequent research would benefit from well‐designed qualitative studies and patient‐centred outcome measures to ensure that the individuality of participants' positive and negative experiences is captured.